2015
DOI: 10.1210/me.2015-1165
|View full text |Cite
|
Sign up to set email alerts
|

SSBP3 Interacts With Islet-1 and Ldb1 to Impact Pancreatic β-Cell Target Genes

Abstract: Islet-1 (Isl1) is a Lin11, Isl1, Mec3 (LIM)-homeodomain transcription factor important for pancreatic islet cell development, maturation, and function, which largely requires interaction with the LIM domain-binding protein 1 (Ldb1) coregulator. In other tissues, Ldb1 and Isl1 interact with additional factors to mediate target gene transcription, yet few protein partners are known in β-cells. Therefore, we hypothesize that Ldb1 and Isl1 participate in larger regulatory complexes to impact β-cell gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…1e ). In αTC1-specific DA peaks, we observed motif enrichment for Fox family member TF (Fox:Ebox dimer, Foxa2, Foxo1, and Foxp1), which are involved in islet alpha cell function as suggested by Foxp1/2/4 knockout mice developing hypoglycemia and having impaired glucagon secretion 47 , and Tal1/Scl, which targets Ldb1 48 , a coregulator of the Lin11-Isl1-Mec3 (LIM)–homeodomain (HD) complex implicated in islet alpha, beta, and delta cell development 49 , 50 . Other enriched TF motifs included Tcf12, which is involved in neural stem cell expansion 51 , and Tfap4/Ap4, a motif that interacts with Igfbp2 52 , a diagnostic and prognostic marker of pancreatic cancer 53 .…”
Section: Resultsmentioning
confidence: 99%
“…1e ). In αTC1-specific DA peaks, we observed motif enrichment for Fox family member TF (Fox:Ebox dimer, Foxa2, Foxo1, and Foxp1), which are involved in islet alpha cell function as suggested by Foxp1/2/4 knockout mice developing hypoglycemia and having impaired glucagon secretion 47 , and Tal1/Scl, which targets Ldb1 48 , a coregulator of the Lin11-Isl1-Mec3 (LIM)–homeodomain (HD) complex implicated in islet alpha, beta, and delta cell development 49 , 50 . Other enriched TF motifs included Tcf12, which is involved in neural stem cell expansion 51 , and Tfap4/Ap4, a motif that interacts with Igfbp2 52 , a diagnostic and prognostic marker of pancreatic cancer 53 .…”
Section: Resultsmentioning
confidence: 99%
“…The recognition of β cell dedifferentiation in type 2 diabetes and the improving but still limited ability of directed differentiation protocols to generate functionally mature β cells (71,(74)(75)(76) support the translational relevance of our findings. Considering that LDB1-mediated complexes recruit chromatinremodeling factors and establish chromatin architecture (21)(22)(23)(24)26), LDB1 represents an attractive therapeutic target positioned at the intersection of the transcriptional networks and epigenetics governing the identities of the pancreatic endocrine lineages.…”
Section: Discussionmentioning
confidence: 99%
“…The LMO-based paradigm is implemented during erythropoiesis and hematopoiesis and involves the formation of a pentameric complex, in which LDB1 binds an LMO factor that in turn bridges a GATA factor and an E-box heterodimer (18)(19)(20). These LDB1-mediated complexes recruit chromatinremodeling complexes and enlist transcriptional machinery (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, our goal was to employ an unbiased reversible cross-link immunoprecipitation (ReCLIP) coupled with mass spectrometry (MS) to compare and characterize the functional protein interactors of the LIM transcriptional complex components Isl1 and SSBP3. We performed an SSBP3 ReCLIP-MS experiment and then compared the dataset with our previously reported Isl1 results (22). We found the ring finger ubiquitin ligase complex components, Rnf20 and Rnf40, in the MS datasets.…”
mentioning
confidence: 86%
“…Comparison of Isl1 and Ldb1 loss-of-function models revealed similar embryonic and adult ␤-cell phenotypes, including dysregulation of key TF genes MafA and Arx (13,21), supporting that these factors cooperatively function to regulate ␤-cell development and function. Recently, we discovered that the ssDNA-binding protein 3 (SSBP3) co-regulator interacts with Isl1 and Ldb1 and is important for ␤-cell function (22). siRNA-mediated knockdown and ChIP studies revealed that SSBP3 regulates and occupies the Isl1/Ldb1 target genes, MafA and Glp1R.…”
mentioning
confidence: 99%